Oridonin Targets Multiple Drug-Resistant Tumor Cells as Determined by in Silico and in Vitro Analyses - Kadioglu, Onat; Saeed, Mohamed; Kuete, Victor; Greten, Henry J.; Efferth, Thomas (Frontiers in Pharmacology, 2018)
Drug resistance is one of the main reasons of chemotherapy failure. Therefore overcoming drug resistance is an invaluable approach to identify novel anticancer drugs that have the potential to bypass or overcome resistance to established drugs and to substantially increase life span of cancer patients for effective chemotherapy. Oridonin is a cytotoxic diterpenoid isolated from Rabdosia rubescens with in vivo anticancer activity. In the present study, we evaluated the cytotoxicity of oridonin towards a panel of drug-resistant cancer cells overexpressing ABCB1, ABCG2 or ΔEGFR or with a knockout deletion of TP53. Interestingly, oridonin revealed lower degree of resistance than the control drug, doxorubicin. Molecular docking analyses pointed out that oridonin can interact with Akt/EGFR pathway proteins with comparable binding energies and similar docking poses as the known inhibitors. Molecular dynamics results validated the stable conformation of oridonin docking pose on Akt kinase domain. Western blot experiments clearly revealed dose-dependent downregulation of Akt and STAT3. Pharmacogenomics analyses pointed to a mRNA signature that predicted sensitivity and resistance to oridonin. In conclusion, oridonin bypasses major drug resistance mechanisms and targets Akt pathway and might be effective towards drug refractory tumors. The identification of oridonin-specific gene expressions may be useful for the development of personalized treatment approaches.